Socialization Of Mangrove Planting In Muara Kembang Village, Muara Jawa District, Kutai Kartanegara Regency - Azham, Zikri; Tirkaamiana, Mohammad Taufan; Jumani, Jumani; Biantary, Maya Preva; Patah, Abdul; Derita, Djumansi; Sugiono, Sugiono (JURNAL ABDIMAS UNTAG SAMARINDA, 2025)
The decline in fishermen’s income has continued to worsen, especially income from shrimp. The Mahakam Delta where they work has experienced damage, particularly its mangrove forests. The community service activity in Muara Kembang Village aims to raise awareness about the importance of mangrove forests. The Wanamina Sejahtera Forest Farmers Group is aware that the decline in shrimp catches is caused by damage to mangrove forests in fish and shrimp catch locations in their area. This has been brought about by increasing exploitation, weak law enforcement, and a lack of public knowledge about the role of the mangrove ecosystem. Community service activities to preserve mangrove forests have received an enthusiastic response, marked by productive and responsive discussions. The Wanamina Sejahtera Forest Farmers Group is able to become an agent of change and encourage the community to plant and preserve mangrove forests